Analysis of the Influence of Post-Pandemic International Trade on Economic Growth in Indonesia - Desember Palito Sinaga; Rianto Irvandinata Lumbangaol; Silvia Agustin Manullang (International Journal of Business and Applied Economics, 2023)
This study aims to determine post-pandemic developments in Indonesia's exports and imports and their impact on economic growth in Indonesia. International trade is an activity or economic activity involving two or more countries to meet the needs of the people of those countries. International trade is where it happens to buy goods and services on a broad scale. This is because trade cooperation is carried out by various countries, and there is a desire to promote certain goods and services freely. With international trade, a country can increase its prosperity and create equity in demand, supply, and services. The research method used in this research is library research, namely collecting information from related documents and photographs to support the writing process.